Pengembangan Potensi Dana Zakat Produktif Melalui Lembaga Amil Zakat Al-Washliyah (LAZ Washol) Untuk Meningkatkan Kesejahteraan Masyarakat - Nabila Ramadhani; Siti Aisyah (LPPM Universitas Labuhanbatu, 2024)
The activity of paying zakat has a vertical relationship with Allah SWT as God and his creatures. The activity of paying zakat also has a horizontal relationship between humans and humans. The purpose of zakat management is to increase the use of zakat results which have an impact on justice, improve the condition of society for the better, minimize poverty levels that require productive zakat and LAZ has a function to improve people's welfare. relating to the development and reduction of the poor who need productive zakat. Collection of data and information obtained through analysis of literature and subsequent interviews were analyzed qualitatively. The results of this study are aimed at developing the potential of productive zakat funds through LAZ to improve people's welfare through various capital financing programs for the poor in accordance with Islamic law in accordance with the utilization of zakat. LAZ also has a role and function to create economic independence for the poor and has a role as a means of religion to increase the benefits of funds and zakat.